A Novel Watermarking and Re-Encryption Approach to Avoid Illegal Content Sharing In Cloud (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing is a set of information stored in a cloud, it can be accessed by the user whenever there is a need to access. Cloud computing is a combination of large interconnected computers. Importance of clod computing are storage and processing power to run application. Information can be access from anywhere .Data management is also one importance of the cloud computing. It improves performance. And also a lower infrastructure cost. Lower bandwidth does not support. Another important disadvantage is security thread. Cloud computing requires a constant internet connection. By using watermarking and re-encryption technique we can overcome the problem of security thread in the cloud. In this article we briefly discuss about the above mentioned technique for implementing to overcome the security thread in the cloud computing.